anudoneddbv

Answered

2022-07-17

Discrete Math Proofs
Are these steps for finding the solutions of $\sqrt{x+3}=3-x$correct?
1. $\sqrt{x+3}=3-x$ is given;
2. $x+3={x}^{2}-6x+9$, obtained by squaring both sides of (1);
3. $0={x}^{2}-7x+6$, obtained by subtracting $x+3$ from both sides of (2);
4. $0=\left(x-1\right)\left(x-6\right)$, obtained by factoring the right-hand side of (3);
5. $x=1$ or $x=6$, which follows from (4) because $ab=0$ implies that $a=0$ or $b=0$.

Answer & Explanation

Clarissa Adkins

Expert

2022-07-18Added 16 answers

Step 1
Those steps are correct, but there's one final step required:
6. When $x=1$, the left-hand side is 2 and the right-hand side is 2; when $x=6$, the left-hand side is 3 and the right-hand side is -3. So only the first "solution" is a solution. (Er. When I did this the first time, I wrongly thought that the RHS in the $x=6$ case was 3.)
To explain step 5: we want to find x, given that $\left(x-1\right)\left(x-6\right)=0$. Let $a=x-1$ and $b=x-6$; then since $ab=0$, we have $a=0$ or $b=0$. So $x-1=0$ or $x-6=0$; so $x=1$ or $x=6$.
Step 2
Why is it the case that if $ab=0$ then $a=0$ or $b=0$? This is precisely the statement that the product of nonzero quantities is nonzero (by taking the contrapositive), which you might find more intuitive; but I see there is another answer which gives algebraic manipulations to prove it.

Damien Horton

Expert

2022-07-19Added 5 answers

Step 1
Yes, all the steps are correct. You only need to check those value of x if it satisfies the original equation or not.
Assume that $ab=0$. We want to show that either $a=0$ or $b=0$.
Step 2
If $a=0$ then we are done. Suppose that $a\ne 0$. Then ${a}^{-1}\in \mathbb{R}$. Thus, using field properties of R we get $b=1b=\left({a}^{-1}a\right)b={a}^{-1}\left(ab\right)={a}^{-1}0=0.$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?